Trial and error : the autobiography of Chaim Weizmann - Weizmann, Chaim; Horovitz, B. (London: Horovitz Publishing Co., 1950)
"Chaim Weizmann ; With 185 illustrations selected and arranged by B. Horovitz Bibliotheek Camille Huysmans"